Penggunaan Sistem Informasi Geografis (Sig) Dalam Analisis Daya Dukung Lahan Berbasis Kemampuan Lahan (Studi Kasus: Wilayah Lahan Kabupaten Banyuasin Tahun 2023) - Hevi Ratna Sari; M. Yusuf Nur Khakim; Erni S (Jurnal Pendidikan Indonesia, 2025)
The increasing need for land for various development activities requires a proper evaluation of the capacity and carrying capacity of the land. This study aims to analyze the carrying capacity of land based on land capabilities in Banyuasin Regency by utilizing Geographic Information System (GIS) technology. The methods used include the collection of spatial data such as soil type, slope slope, land use, rainfall, and actual land use data, which are then processed using GIS software to overlay and classify land capabilities. The results of the study show that most of the Banyuasin Regency area is in land capability classes III and IV, which have moderate to high limitations on land use intensity. Several areas were identified as experiencing utilization pressure that exceeded their carrying capacity, characterized by the conversion of agricultural land into residential and industrial areas. These findings provide an idea that spatial planning and land use in the region need to be aligned with land capabilities in order for sustainable development to be realized. GIS has proven to be effective as an aid in spatial analysis to support geospatial data-driven decision-making.